Synchronization of an uncertain Duffing oscillator with higher order chaotic systems - Kabziński, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
The problem of practical synchronization of an uncertain Duffing oscillator with a higher order chaotic system is considered. Adaptive control techniques are used to obtain chaos synchronization in the presence of unknown parameters and bounded, unstructured, external disturbances. The features of the proposed controllers are compared by solving Duffing-Arneodo and Duffing-Chua synchronization problems.
Keywords: chaos synchronization; adaptive control; Duffing oscillator